ANALISIS ANGGARAN PROYEK SEBAGAI ALAT PENGENDALIAN BIAYA PADA PERUSAHAAN KONTRAKTOR CV. WIJAYA CIPTA MANDIRI - Ida Rahmawati3, Isnawati Imam Nazarudin Latif (EKONOMIA, 2020)
The purpose of this study is to analyse the budget plan and the cost realization in Procurement and Installation of Pipeline Distribution Service Project at Rapak Lambur Village. The research data of this study was obtained directly from secondary data in form of the budget plan and its realization which is obtained directly from the company and also direct interview with company side.         This study used analysis of variant, which is if the budget project cost more than its realization then there will be a beneficiary difference, meanwhile if the budget project cost less than its realization then there will be a disadvantageous difference.         Project of Procurement and Installation Pipeline of Distribution Service at Rapak Lambur village, founded a favourable difference Rp. 51,590,876.00 for materials, favourable difference around Rp. 7,640,000.00 for the labour, and a profitable difference of Rp. 1,832,282.60 for project overhead costs. Cost control is done as a result of the existence of an unfavorable difference between the budget and the realization of project costs.         Based on the results of this study indicate that the function of the project cost budget plan made by the company functions well as a cost control tool for the company.